2003
DOI: 10.1111/j.1749-6632.2003.tb03253.x
|View full text |Cite
|
Sign up to set email alerts
|

The Mesenchymal Stroma Negatively Regulates B Cell Lymphopoiesis through the Expression of Activin A

Abstract: The negative control of B cell generation is only partially resolved. We assessed the role of activin A in regulation of B lymphopoiesis in view of its specific inhibitory effects on tumor B lineage cells. Activin A is constitutively expressed in mouse hemopoietic organs and in cultured mesenchymal cell lines. We observed an inverse relationship between activin A titer and B lineage cell production. In the spleen, the red pulp exhibited a relatively higher abundance of the protein as compared with the lymphoid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 23 publications
0
21
0
Order By: Relevance
“…83 Moreover, in vivo polyclonal B-cell activation induced by LPS injection was accompanied by a notable reduction of bA expression in bone marrow and spleen (Figure 3a). 84 Several experiments have shown that the inhibitory signals provided by activin A occur at early stages of B-cell development. Analysis of B-cell lymphopoiesis in vitro showed that functional activin A is observed at early stage of cultures, whereas the appearance of B220 + B-cell colonies correlated with a lower titer of functional activin A and high levels of FS and inhibin a-chain expression (Figure 3a).…”
Section: Role Of Activins/inhibins On Adaptive Immune Cells B Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…83 Moreover, in vivo polyclonal B-cell activation induced by LPS injection was accompanied by a notable reduction of bA expression in bone marrow and spleen (Figure 3a). 84 Several experiments have shown that the inhibitory signals provided by activin A occur at early stages of B-cell development. Analysis of B-cell lymphopoiesis in vitro showed that functional activin A is observed at early stage of cultures, whereas the appearance of B220 + B-cell colonies correlated with a lower titer of functional activin A and high levels of FS and inhibin a-chain expression (Figure 3a).…”
Section: Role Of Activins/inhibins On Adaptive Immune Cells B Cellsmentioning
confidence: 99%
“…85 Conversely, the use of a mouse endothelialadipocyte cell line, which lacks functional activin A, resulted in the early accumulation of CD43 lo B220 À and CD43 lo B220 + B-cell colonies. 84 Hence, activin A behaves as a ''brake'' signal on B-cell differentiation under steady conditions, but once inflammatory signals have emerged, such as those triggered by LPS, activin A expression in the bone marrow is turned off, allowing B-cell differentiation and the expansion of the B-cell repertoire (Figure 3a).…”
Section: Role Of Activins/inhibins On Adaptive Immune Cells B Cellsmentioning
confidence: 99%
“…The observed differentiation of intestinal tissue from pancreas by supplemented activin A closely resembles our observations including onset of Shh and iFABP expression. Activin A is constitutively expressed by the mesenchymal spleen stroma (Shoham et al 2003). bSM and wild-type splenic mesenchyme (wSM) isolated at e13.5 were positive for the Activin ␤A subunit by RT-PCR (Fig.…”
Section: Wild-type Spleen Mesenchyme Induces Cyst Formationmentioning
confidence: 99%
“…8,9 Contrary to their well-known effect on T cells and antigen-presenting cells, the effect of MSC on B cells remains unclear. MSC have been implicated in B-cell development, in bone marrow, spleen and lymphoid follicles, 10 exerting a negative control on B-cell lymphopoiesis through the expression of activin A, a pleiotropic molecule which is a member of the transforming growth factor-β superfamily. In addition, Corcione et al reported that B-cell proliferation is inhibited by MSC, 11 but this has not been confirmed by other authors.…”
Section: Introductionmentioning
confidence: 99%